2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.26028
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Engineering Students How to Recognize and Analyze Ethical Scenarios

Abstract: Insufficient formal training in how to identify and navigate ethical situations can leave undergraduate engineering students undervaluing the significance of ethics in their future professional lives. Based on previous literature, we hypothesized that integrating an ethics component into previously established engineering courses will highlight the relevance of ethics in technical studies and provide skills for ethical decision making. However, incorporating ethics into engineering curricula is often hindered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…They recommend the inclusion of ethical theory course content that specifically includes this concept, as students do not gain this understanding through a typical case study based curriculum. This and other studies make a case for supplementing case study instruction with ethical instruction that is more closely tied with course content and every day decisions [5,10,11,12]. The use of case study examples where there is a correct answer and where there is a clear tragic outcome or heroic action suggests that ethical decisions are a once in a career event of major consequence.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…They recommend the inclusion of ethical theory course content that specifically includes this concept, as students do not gain this understanding through a typical case study based curriculum. This and other studies make a case for supplementing case study instruction with ethical instruction that is more closely tied with course content and every day decisions [5,10,11,12]. The use of case study examples where there is a correct answer and where there is a clear tragic outcome or heroic action suggests that ethical decisions are a once in a career event of major consequence.…”
Section: Introductionmentioning
confidence: 96%
“…So, how can this best be included in an engineering curriculum? Herkert [6] recommends that systematic inclusion of ethics within a curriculum is required, and studies have shown the effectiveness of across-the-curriculum models [10,11]. Survey results have also shown that faculty support ethics inclusion in multiple courses, and propose that ethics inclusion only in freshmen and senior classes can be detrimental by isolating ethics from the technical content, implying that students should prioritize the technical over the ethical [3,19].…”
Section: Introductionmentioning
confidence: 99%